Surgical resection of a colonic haemangiosarcoma in a cat. Issue 2 (8th April 2021) - Rivenburg, Rachel; Gailbreath, Katherine; Campbell, Kathryn; Maxwell, Elizabeth A.
Abstract: A 14‐year‐old male neutered Ragdoll was presented for hyporexia, lethargy and tenesmus. A mass associated with the descending colon was noted on exploratory laparotomy. A resection and anastomosis of the colonic mass and extirpation of a colonic lymph node was performed. A colonic mural haemangiosarcoma with colonic lymph node metastasis was diagnosed on histopathology. The cat was humanely euthanized 109 days postoperatively for anorexia, haematemesis and hind limb ataxia. Intestinal haemangiosarcoma should be a differential for colonic masses in cats. Surgical resection can provide good short‐term outcomes and should be considered as a treatment option for feline colonic haemangiosarcoma.